Effect of music on children’s nature and behaviour. How music can educate, but also destroy - E. Georgieva (Trakia Journal of Sciences)
This article raises the question of the influence of music on the physical, emotional and mental development of children. Why has it got such power? What are the powerful effects it has on the brain? What is the counterproductive influence of music? Which music develops the virtues and which destroys? These are questions the answers to which were known even to ancient philosophers.